Correlations of IL-1 and IL-6 Gene polymorphisms with hypertrophic cardiomyopathy: IL-1 and IL-6 in hypertrophic cardiomyopathy - Liu, Nanchao; Liu, Chaoquan; Wu, Yongning; Li, Haili (Cellular and Molecular Biology, 2024)
The purpose of this study was to explore the correlations of interleukin-1 (IL-1) and IL-6 gene polymorphisms with hypertrophic cardiomyopathy (HCM). A total of 200 patients with HCM were enrolled as disease group, and 200 healthy individuals were included as control group. Peripheral blood was collected from all subjects in both disease and control groups. Gene polymorphisms and serum expression levels of IL-1 and IL-6 were detected, and conjoint analysis was performed based on results of cardiac color Doppler ultrasound examination. The allele distribution of IL-1 rs1878320 showed a difference between disease and control groups (P=0.000). The frequency of the allele T was lower in disease group. The genotype distribution of IL-1 rs1878320 (P=0.001) and IL-6 rs1474347 (P=0.000) in disease group was different from that in control. The frequency of TC genotype of IL-1 rs1878320 was lower in disease group, and that of CA genotype of IL-6 rs1474347 was higher in disease group. There was a difference in the distribution of the dominant model of IL-6 rs1474347 between disease and control groups (P=0.021), and the frequency of CC + CA in the dominant model was 171 (0.855). The frequency of AC haplotype of IL-1 gene was overtly higher in disease group (P=0.000), while the frequency of AT haplotype was lower in disease group (P=0.000). The IL-1 rs1516792 polymorphism had an association with serum IL-1 level (P<0.05), the IL-1 level was notably increased in the patients with the genotype AA, and it was higher in disease group. The polymorphism of rs1878320 locus in IL-1 gene was correlated with interventricular septal (IVS) (P=0.047), and IVS was reduced in the patients with TC genotype. The polymorphism of rs1516792 locus in IL-1 gene was distinctly related to left ventricular outflow tract (LVOT) (P=0.041), and LVOT was lowered in the patients with GG genotype. The IL-6 rs2069831 polymorphism was associated with left ventricular ejection fraction (LVEF) (P=0.035), and LVEF declined in the patients with TT genotype. The IL-1 and IL-6 gene polymorphisms are correlated with the susceptibility and progression of HCM.